Phenyllactic acid production by simultaneous saccharification and fermentation of pretreated sorghum bagasse. (April 2015) - Kawaguchi, Hideo; Teramura, Hiroshi; Uematsu, Kouji; Hara, Kiyotaka Y.; Hasunuma, Tomohisa; Hirano, Ko; Sazuka, Takashi; Kitano, Hidemi; Tsuge, Yota; Kahar, Prihardi; Niimi-Nakamura, Satoko; Oinuma, Ken-Ichi; et al.
Graphical abstract: Highlights: Phenyllactate was produced from dilute acid-pretreated sorghum bagasse by SSF. Sorghum bagasse yielded fermentation inhibitors of aldehyde and phenolic acid. Sorghum bagasse altered metabolic profiles during phenyllactate fermentation. SSF yielded 4.8-fold more phenyllactate than separate hydrolysis and fermentation. Abstract: Dilute acid-pretreated sorghum bagasse, which was predominantly composed of glucan (59%) and xylose (7.2%), was used as a lignocellulosic feedstock ford -phenyllactic acid (PhLA) production by a recombinant Escherichia coli strain expressing phenylpyruvate reductase from Wickerhamia fluorescens . During fermentation with enzymatic hydrolysate of sorghum bagasse as a carbon source, the PhLA yield was reduced by 35% compared to filter paper hydrolysate, and metabolomics analysis revealed that NAD(P)H regeneration and intracellular levels of erythrose-4-phosphate and phosphoenolpyruvate for PhLA biosynthesis markedly reduced. Compared to separate hydrolysis and fermentation (SHF) with sorghum bagasse hydrolysate, simultaneous saccharification and fermentation (SSF) of sorghum bagasse under glucose limitation conditions yielded 4.8-fold more PhLA with less accumulation of eluted components, including p -coumaric acid and aldehydes, which inhibited PhLA fermentation. These results suggest that gradual enzymatic hydrolysis during SSF enhances PhLA production under glucose limitation and reduces the accumulation of fermentation inhibitors, collectively leading to increased PhLA yield.